Impact of adopting quick response and agility on supply chain competition with strategic customer behavior - Kaviyani-Charati, M; Ghodsypour, S H; Hajiaghaei-Keshteli, M (Scientia Iranica. Transaction E, Industrial engineering, 2022)
A growing trend towards computerization and competition in supply chains results in uncertainty and quick variability that make the decisions difficult for both levels of retailers and manufacturers. In this paper, two Bi-Level Stackelberg Models (BLSMs) are developed under non- and agile conditions in the presence of strategic customers. Our main novelty approach in this paper is to consider both levels competing with each other in a sequential game to determine the optimal production and order quantities and prices with and without agile abilities. In addition, both proposed models are simplified single-level using the Karush-Kuhn-Tucker (KKT) approach. Then, they are remodeled by a Robust Optimization (RO) technique due to existing uncertain parameters. To have a better assessment of the models' efficiency and applicability, they have been implemented in a real case and finally, the results are compared and analyzed.